Teacher Candidates' Perspectives on the Value of a Site-Based Methods Course. Issue 4 (1st October 2020) - Symons, Carrie; Anderson, Blythe E.; Ward, Amy
Abstract: In the field of teacher education, the disconnect between university-based coursework and practical field experiences has long been a concern. To make teacher preparation coursework more meaningful, some programs partner with P-12 schools to offer site-based courses. Although situated learning for novices in practice-based professions makes sense, more research is needed to determine if, how, and why site-based courses in particular may be beneficial for teacher candidates' (TCs) learning. In this study, we used surveys and interviews with TCs, who had taken the same site-based literacy methods course, to identify which aspects of the course they found most facilitative of connections between the course content and the field. Our findings suggest working with children in classrooms, course instructors' involvement at the school, and opportunities to discuss and reflect upon their experiences immediately after they had been in the field were the primary features of a site-based course TCs found valuable.